Olfaction and Environment: Tsimane’ of Bolivian Rainforest Have Lower Threshold of Odor Detection Than Industrialized German People - Sorokowska, Agnieszka; Sorokowski, Piotr; Hummel, Thomas; Huanca, Tomas (PLOS ONE, 2013)
Olfactory sensitivity varies between individuals. However, data regarding cross-cultural and inter-group differences are scarce. We compared the thresholds of odor detection of the traditional society of Tsimane’ (native Amazonians of the Bolivian rainforest; n = 151) and people living in Dresden (Germany; n = 286) using “Sniffin’ Sticks” threshold subtest. Tsimane’ detected n-butanol at significantly lower concentrations than the German subjects. The distribution of thresholds of the Tsimane’ was very specific, with 25% of Tsimane’ obtaining better results in the olfactory test than any member of the German group. These data suggest that differences in olfactory sensitivity seem to be especially salient between industrialized and non-industrialized populations inhabiting different environmental conditions. We hypothesize that the possible sources of such differences are: (i) the impact of pollution which impairs the olfactory abilities of people from industrialized countries; (ii) better training of olfaction because of the higher importance of smell in traditional populations; (iii) environmental pressures shaping olfactory abilities in these populations.